Impact of Coronary Artery Disease and Percutaneous Coronary Intervention on Transcatheter Aortic Valve Implantation - Anthony G. Matta; Thibault Lhermusier; Francisco Campelo Parada; Frederic Bouisset; Ronan Canitrot; Vanessa Nader; Stéphanie Blanco; Meyer Elbaz; Jerome Roncalli; Didier Carrié (Journal of Interventional Cardiology)
Introduction. The prevalence of coronary artery disease (CAD) detected in preoperative work-up for transcatheter aortic valve implantation (TAVI) is high. Instead, the management of a concomitant CAD remains unclear. We evaluate the impact of CAD and percutaneous coronary intervention (PCI) on TAVI procedures. Materials and Methods. A retrospective study was conducted on 1336 consecutive patients who underwent TAVI in Toulouse University Hospital, Rangueil, France. The studied population was divided into 2 groups: CAD-TAVI group and No CAD-TAVI group. Then, the CAD-TAVI group was segregated into 2 subgroups: PCI-TAVI group and No PCI-TAVI group. In-hospital adverse clinical outcomes were assessed in each group. Results. Pre-TAVI work-up revealed significant CAD in 36% of 1030 patients eligible for inclusion in the study. The overall prevalence of in-hospital death, stroke, major or life-threatening bleeding, minor bleeding, major vascular complications, minor vascular complications, pacemaker implantation, and acute kidney injury was 2.7%, 2.4%, 2.8%, 3.6%, 3.9%, 7.5%, 12.5%, and 2.7%, respectively. Among the studied population, 55% were admitted to the cardiac care unit. No significant statistical difference was observed between groups. Discussion. CAD-TAVI population was not more likely to develop in-hospital adverse clinical outcomes post-TAVI procedure compared to others. Also, no significant difference regarding in-hospital death was observed. In parallel, performing PCI prior to TAVI did not increase the risk of in-hospital death and complications. The difference in terms of the distribution of antithrombotic regimen may explain the higher prevalence of bleeding events in the PCI-TAVI group. Conclusion. This study provides direct clinical relevance useful in daily practice. No negative impact has been attributed to the presence of a concomitant CAD and/or preoperative PCI on the TAVI hospitalization period.